Age-Related Changes in Sperm Morphology and Analysis of Multiple Sperm Defects - Maxim Kleshchev; Ludmila Osadchuk; Alexander Osadchuk (Frontiers in Bioscience-Scholar, 2023)
Background: Analysis of sperm morphology defects (amorphous heads, abnormal acrosome, etc.) is useful for estimating the efficiency of spermiogenesis and sperm maturation. An advanced paternal age (more than 40 years) is associated with decreasing sperm count and reduced motility; however, there is little information on the effect of aging relating to sperm morphological defects. Moreover, searching for stable combinations of certain morphological defects in the same sperm can be useful for better understanding spermiogenesis. The aim of the study was to investigate age-related changes in sperm morphology and the prevalence of certain combinations of sperm morphological defects in men from the general population. Methods: Sperm morphology was assessed in 1266 volunteers from the Russian urban general population in different age groups (18–19, 20–24, 25–29, 30–34, 35–40, and over 40 years old). Two hundred sperm were evaluated from each semen sample (about 250 thousand spermatozoa in total). Sperm defects were classified according to the WHO laboratory manual (WHO, 2010). The total percentage of each sperm defect and the frequency of different combinations of sperm morphological anomalies for each age group were counted. Additionally, a similar analysis was performed for the groups of normospermia and pathozoospermia. Results: The frequency of coiled and short sperm tails increased in men over 40 years old compared to younger subjects; however, aging did not affect the percentage of morphologically normal sperm. It was shown that the combination of a misshaped head (amorphous, pyriform, and elongated) with a postacrosomal vacuole, acrosome defect, excess residual cytoplasm, or any anomaly of the midpiece or tail in the same spermatozoon were not random combinations of independent solitary defects. The increased frequency of combinations of coiled tails with amorphous, elongated, or vacuolated heads was observed in men older than 40 years. Sperm morphological defects, such as severely deformed heads (pyriform, elongated, and round) were more common in men with pathozoospermia compared to normospermic subjects. Conclusions: An age-related impairment in sperm morphology was found. Stable combinations of head defects with anomalies in the acrosome, midpiece or tail suggest that these defects may be the result of a general violation in the morphogenetic mechanism.